2022
DOI: 10.3390/nano12234294
|View full text |Cite
|
Sign up to set email alerts
|

Black TiO2-Based Dual Photoanodes Boost the Efficiency of Quantum Dot-Sensitized Solar Cells to 11.7%

Abstract: Quantum dot−sensitized solar cells (QDSSC) have been regarded as one of the most promising candidates for effective utilization of solar energy, but its power conversion efficiency (PCE) is still far from meeting expectations. One of the most important bottlenecks is the limited collection efficiency of photogenerated electrons in the photoanodes. Herein, we design QDSSCs with a dual−photoanode architecture, and assemble the dual photoanodes with black TiO2 nanoparticles (NPs), which were processed by a femtos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It is revealed that the synthesis of black TiO 2 introduced some defects in the crystal structure, and Ti 3+ can be seen at 458.6 and 464.2 eV, respectively . The peak at 530.4 eV is evidence for the Ti–O linkage, and the peak located at 532.7 eV is attributed to the availability of oxygen vacancies . The results indicate that the as-synthesized black TiO 2 has a large number of Ti 3+ defects and oxygen vacancies.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…It is revealed that the synthesis of black TiO 2 introduced some defects in the crystal structure, and Ti 3+ can be seen at 458.6 and 464.2 eV, respectively . The peak at 530.4 eV is evidence for the Ti–O linkage, and the peak located at 532.7 eV is attributed to the availability of oxygen vacancies . The results indicate that the as-synthesized black TiO 2 has a large number of Ti 3+ defects and oxygen vacancies.…”
Section: Resultsmentioning
confidence: 87%
“…34 The peak at 530.4 eV is evidence for the Ti−O linkage, and the peak located at 532.7 eV is attributed to the availability of oxygen vacancies. 35 The results indicate that the as-synthesized black TiO 2 has a large number of Ti 3+ defects and oxygen vacancies.…”
Section: Xrd Investigationsmentioning
confidence: 90%